2w(-6-1)=

Simple and best practice solution for 2w(-6-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2w(-6-1)= equation:


Simplifying
2w(-6 + -1) = 0

Combine like terms: -6 + -1 = -7
2w(-7) = 0

Reorder the terms for easier multiplication:
2 * -7w = 0

Multiply 2 * -7
-14w = 0

Solving
-14w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Divide each side by '-14'.
w = 0

Simplifying
w = 0

See similar equations:

| 20x^2-27x=14 | | 2x+9=29-3x | | 58-7x=29x+18 | | t^2-t+1=0 | | 4x+5=6x-7 | | x^2-5xy+4y^2=0 | | 3x*(-5xy)=a | | 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x | | 14x=-7 | | -35=5y | | -20=-5y | | 63=9y | | c^2=7c+18 | | -m^2-12=87 | | 4x+38=7x+20 | | X^2+4x^2+24x+24=4x^2+24x+36 | | 7+5a=8+2a | | 2x-3(x+6)=-4x(x-1) | | 7+7a+5a^2=8+2a+2a^2 | | 3y^2+10y=17y^2 | | -9x+4=2x+24 | | b^2+10b+9=0 | | 3(4x-1)=2(5x+4) | | 5x+7y=6 | | 6x-7=m | | 75-4x=32x+23 | | 3t-4=y | | (x+6)(x-2)=-7 | | V-3d=z |

Equations solver categories